Repurposing of phosphodiesterase-5 inhibitor sildenafil as a therapeutic agent to prevent gastric cancer growth through suppressing c-MYC stability for IL-6 transcription - Zhenzhan Zhang; Wuqing Huang; Donghua Huang; Zhou Xu; Qingfeng Xie; Xin Tan; Wenjun He; Weihao Yang; Guoxin Li; Jianguang Ji; Hao Liu (Communications Biology)
Abstract Phosphodiesterase-5 (PDE5) inhibitors have shown promise as anti-cancer agents in malignancies. However, their specific effects on gastric cancer (GC) and the underlying mechanisms remain elusive. Our aim was to investigate this by combining evidence from population-based studies with data obtained from in vivo and in vitro experiments. By combing a couple of nationwide Swedish registers, GC patients who received PDE5 inhibitors were compared to matched controls while adjusting for confounding factors. The anti-tumor effect and mechanism of the PDE5 inhibitor sildenafil were evaluated via using tumor cells, patient-derived tumor organoids and xenograft animal models in GC. A total of 161 Swedish GC patients from a nationwide population-based cohort who received post-diagnostic PDE5 inhibitors demonstrated lower cancer-specific mortality compared to the controls (HR = 0.66, 95% CI = 0.47-0.92, P = 0.016). Functionally, the PDE5 inhibitor sildenafil exhibited the suppressive ability to prevent oncogenic growth in GC. Mechanistically, sildenafil restrained GC growth by directly activating PKG through PDE5 inhibition for regulating c-MYC expression via its phosphorylation and ubiquitination degradation, thereby suppressing c-MYC stability for IL-6 transcription within the downstream IL-6/JAK/STAT3 signalling pathway. The PDE5 inhibitor sildenafil may serve as a promising adjuvant for GC therapy if further randomized clinical trials confirm its efficacy.